Basophils and Eosinophils in Nematode Infections - Obata-Ninomiya, Kazushige; Domeier, Phillip P.; Ziegler, Steven F. (Frontiers in Immunology, 2020)
Helminths remain one of the most prolific pathogens in the world. Following infection helminths interact with various epithelial cell surfaces, including skin, lung and gut. Recent works have shown that epithelial cells produce a series of cytokines such as TSLP, IL-33, and IL-25 that lead to the induction of innate and acquired type 2 immune responses, which we named Type 2 epithelial cytokines. Although basophils and eosinophils are relatively rare granulocytes under normal conditions (0.5% and 5% in peripheral blood, respectively), both are found with increased frequency in type 2 immunity, including allergy and helminth infections. Recent reports showed that basophils and eosinophils not only express effector functions in type 2 immune reactions, but also manipulate the response towards helminths. Furthermore, basophils and eosinophils play non-redundant roles in distinct responses against various nematodes, providing the potential to intervene at different stages of nematode infection. These findings would be helpful to establish vaccination or therapeutic drugs against nematode infections.